Mechanisms Underlying the Strong Inhibition of Muscle-Type Nicotinic Receptors by Tetracaine - Cobo, Raúl; Nikolaeva, Magdalena; Alberola-Die, Armando; Fernández-Ballester, Gregorio; González-Ros, José M.; Ivorra, Isabel; Morales, Andrés (Frontiers in Molecular Neuroscience, 2018)
Nicotinic acetylcholine (ACh) receptors (nAChRs) are among the targets of a variety of local anesthetics (LAs), although the molecular mechanisms of blockade are yet poorly understood. Some LAs, as lidocaine, act by different means on nAChRs because of their presence as charged and uncharged forms. Thus, we have now explored the mechanisms of nAChR blockade by tetracaine (Ttc), which, at physiological pH, is almost exclusively present as a positively charged LA. nAChRs from Torpedo electroplaque were transplanted to Xenopus oocytes and the currents elicited by ACh (IAChs), either alone or co-applied with Ttc, were recorded. Ttc reversibly blocked IACh, with an IC50 in the submicromolar range. Noticeably, at very low concentrations (0.1 µM), Ttc only reduced IACh in a voltage-dependent manner, the more negative potentials the higher inhibition, indicating open-channel blockade. When Ttc concentration rose to 0.7 µM, or above, a voltage-independent inhibition was added, evidencing a closed-channel blockade. IACh inhibition by just 0.7 µM Ttc pre-application before ACh superfusion also corroborates the Ttc blockade of resting nAChRs. Furthermore, Ttc markedly increased nAChR desensitization, mainly at concentrations equal or higher than 0.5 µM. Interestingly, Ttc did not modify desensitization when preventing its binding within the channel pore by holding the membrane at positive potentials. Ttc-nAChRs interactions were assessed by virtual docking assays, using nAChR models in the closed and open states. These assays revealed that Ttc binds at different sites of the nAChR, involving extracellular and transmembrane domains, in both open- and closed-conformations. Extracellular binding sites seem relevant for the closed-channel blockade whereas two sites within the pore, with different affinities for Ttc, would contribute to open-channel blockade and enhancement of desensitization, respectively. These results demonstrate a concentration-dependent heterogeneity of Ttc actions on nAChRs and contribute to the understanding of the complex modulation of muscle-type nAChRs by LAs. Furthermore, the combination of functional- and virtual-assays to decipher nAChR-Ttc interactions has allowed us to launch a tentative assignment of the main nAChR residues involved in these modulating actions.